2016
DOI: 10.1364/boe.7.003211
|View full text |Cite
|
Sign up to set email alerts
|

In vitro neuronal depolarization and increased synaptic activity induced by infrared neural stimulation

Abstract: Neuronal responses to infrared neural stimulation (INS) are explored at the single cell level using patch-clamp electrophysiology. We examined membrane and synaptic responses of solitary tract neurons recorded in acute slices prepared from the Sprague-Dawley rat. Neurons were stimulated using a compact 1890 nm waveguide laser with light delivered to a small target area, comparable to the size of a single cell, via a single-mode fiber. We show that infrared radiation increased spontaneous synaptic event frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…However, a simulation study showed that the shift in membrane capacitance required to depolarize an axon would not likely be achieved using the parameters typically used in INS . Furthermore, a recent in vitro study in acute mammalian brainstem slices highlighted the possibility of evoking inward currents in individual neurons with low power densities, which would suggest that the fast temperature gradient is not necessarily needed .…”
Section: Introductionmentioning
confidence: 99%
“…However, a simulation study showed that the shift in membrane capacitance required to depolarize an axon would not likely be achieved using the parameters typically used in INS . Furthermore, a recent in vitro study in acute mammalian brainstem slices highlighted the possibility of evoking inward currents in individual neurons with low power densities, which would suggest that the fast temperature gradient is not necessarily needed .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional electrical stimulation, INS uses fiber-optic coupling laser to stimulate nerve tissue, which solves the problem of mechanical damage caused by contact electrodes in electrical stimulation; meanwhile, laser stimulation has good spatial accuracy, which can stimulate a single neuron without range effect; in addition, the stimulus signal does not affect the detected response signal because of the difference between the nature of stimulation (light signal) and response (electrical signal). It is also examined that infrared radiation increases the frequency of spontaneous synaptic events and the response size is proportional to the output of the excitation light [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Entwisle et al have detected the membrane and synaptic responses of solitary tract neurons recorded in acute sections of rats. They used a 1890 nm compact waveguide laser to stimulate neurons and send light through a single-mode fiber to a small target the size of a single cell and found that the response was proportional to the laser output [ 79 ]. A thulium-doped glass waveguide laser is used in the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Using these lower-cost diode systems (∼$20k), multiple groups published results demonstrating the efficacy of 1875 nm and 1450 nm light for eliciting neural activity. 9 , 22 , 26 , 27 , 30 32 , 36 51 Custom diode systems can be made for a few thousand dollars but require some proficiency in laser hardware and electronics. Other groups opted to use fiber lasers with tunable thulium fiber lasers centered around 2000 nm being the most common, but this wavelength may be too strongly absorbed by water in the tissue.…”
Section: Introductionmentioning
confidence: 99%